Biphasic behaviors and regeneration energy of a 2-(diethylamino)-ethanol and 2-((2-aminoethyl)amino) ethanol blend for CO2 capture. Issue 12 (29th October 2019) - Liu, Fei; Fang, Mengxiang; Yi, Ningtong; Wang, Tao; Wang, Qinhui
Abstract : Using the biphasic solvent for CO2 capture is a novel strategy to reduce the effect of increased viscosity on the regeneration energy. Abstract : High regeneration energy is one of the bottlenecks of traditional monoethanolamine (MEA) technology for CO2 capture. A novel process using a biphasic solvent is a potential solution towards a significant reduction in the regeneration energy. A 2-(diethylamino)-ethanol (DEEA) and 2-((2-aminoethyl)amino) ethanol (AEEA) blend is a promising biphasic solvent with high stability and low cost. The biphasic behavior of CO2 absorption in the DEEA/AEEA blend was investigated to optimize CO2 capacity and minimize the regeneration energy. 60% DEEA/20% AEEA is the optimal biphasic solvent with 60% higher CO2 capacity and 44% lower regeneration energy than that of the conventional MEA solvent. 13 C NMR analysis was performed to reveal the phase separation mechanism. CO2 reaction products of amine carbamates and bicarbonate (HCO3 − /CO3 2− ) accumulate in the CO2 -rich phase while unreacted DEEA and AEEA migrate to the CO2 -lean phase. Only sending the CO2 -rich phase into the stripper enables to increase CO2 partial pressure and reduce the heat duty. On the other hand, a significant increase in the viscosity of the CO2 -rich phase increases the energy penalty by decreasing the heat transfer coefficient of the heat exchanger. Due to the phase separation, the regeneration energy of the DEEA/AEEA biphasic solvent is less affected by the increased viscosity compared to other water-lean solvents. A normalized factor was proposed to incorporate both effects of increased viscosity and phase separation on the regeneration energy of the biphasic solvent.